Comparing Aging and Fitness Effects on Brain Anatomy - Fletcher, Mark A.; Low, Kathy A.; Boyd, Rachel; Zimmerman, Benjamin; Gordon, Brian A.; Tan, Chin H.; Schneider-Garces, Nils; Sutton, Bradley P.; Gratton, Gabriele; Fabiani, Monica (Frontiers in Human Neuroscience, 2016)
Recent studies suggest that cardiorespiratory fitness (CRF) mitigates the brain’s atrophy typically associated with aging, via a variety of beneficial mechanisms. One could argue that if CRF is generally counteracting the negative effects of aging, the same regions that display the greatest age-related volumetric loss should also show the largest beneficial effects of fitness. To test this hypothesis we examined structural MRI data from 54 healthy older adults (ages 55-87), to determine the overlap, across brain regions, of the profiles of age and fitness effects. Results showed that lower fitness and older age are associated with atrophy in several brain regions, replicating past studies. However, when the profiles of age and fitness effects were compared using a number of statistical approaches, the effects were not entirely overlapping. Interestingly, some of the regions that were most influenced by age were among those not influenced by fitness. Presumably, the age-related atrophy occurring in these regions is due to factors that are more impervious to the beneficial effects of fitness. Possible mechanisms supporting regional heterogeneity may include differential involvement in motor function, the presence of adult neurogenesis, and differential sensitivity to cerebrovascular, neurotrophic and metabolic factors.